Implementasi Penggunaan Personal Protective Equipment (PPE) oleh housekeeper di Cordela Suites Tasikmalaya - Indah Sugiarti; Moh. Abdul Azis Danu Brata (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The use of Personal Protective Equipment (PPE) is an important aspect in maintaining the occupational health and safety of housekeepers in the hospitality industry. Housekeepers are exposed to various occupational risks that require adequate protection. This study aims to analyze the implementation of PPE usage by housekeepers at Cordela Suite Tasikmalaya Hotel, including knowledge, usage practices, supporting and inhibiting factors, as well as workers' perceptions toward PPE. This research is a descriptive qualitative study with an observational approach and in-depth interviews. Respondents include the Executive Housekeeper, Room Attendant, and Order Taker. Data were collected through observation sheets and structured interview guidelines, then analyzed descriptively. Observation results show that housekeepers use PPE according to Standard Operating Procedures (SOP), including masks, gloves, and shoes in proper working condition. PPE storage facilities and information boards for usage are available. Supervision is conducted directly with warnings given to those who do not follow procedures. The main constraint is discomfort (heat) especially for internship participants, but it remains mandatory to maintain hygiene. In conclusion, the implementation of PPE usage at Cordela Suite Tasikmalaya has been running well with adequate availability, strict supervision, and high awareness among workers. Enhancement of basic housekeeping understanding for prospective workers is needed to improve PPE usage compliance.